Global mapping of meiotic recombination hotspots and coldspots in the yeast Saccharomyces cerevisiae - Gerton, Jennifer L. (The National Academy of Sciences, 2000)
In the yeast Saccharomyces cerevisiae, meiotic recombination is initiated by double-strand DNA breaks (DSBs). Meiotic DSBs occur at relatively high frequencies in some genomic regions (hotspots) and relatively low frequencies in others (coldspots). We used DNA microarrays to estimate variation in the level of nearby meiotic DSBs for all 6,200 yeast genes. Hotspots were nonrandomly associated with regions of high G + C base composition and certain transcriptional profiles. Coldspots were nonrandomly associated with the centromeres and telomeres.